Numerical simulation and visualization in problems of studying space debris dynamics - Kucheryavchenko, N. A. (Russian physics journal)
We present a description of the application SDVEApp designed to conduct research on the dynamic evolution of near-Earth space objects, namely, for calculation and visualization of the near-Earth object characteristics frequently used in research. In addition, the application makes it easier to work with a number of well-known catalogs of space objects. We demonstrate the results of application of the developed software to a set of objects from the NORAD and ESA Classification of geosynchronous objects catalogs, as well as objects, data on which were obtained from observations made by the employees of the Department of Celestial Mechanics and Astrometry of the Research Institute of PMM TSU.